Power system flexibility: A review - O. M. Babatunde; J. L. Munda; Y. Hamam (Energy Reports, 2020)
Power systems networks are traditionally structured and engineered to effectively accommodate the effects of uncertainty and variability as regards energy demand and availability of resources. In order to transform the present carbon-intensive electricity generation system to one driven largely by clean energy sources, the inclusion of variable renewable energy sources (vRES) is becoming predominant. However, the inclusion of large vRES in the power plant mix increases the uncertainty, variability and consequently flexibility requirements on the power system network. The inclusion of cost effective and environment friendly flexible generators that can cancel the effects of uncertainty and variability is essential on power system networks with high levels of vRES. This study highlights flexibility as it relates to energy transition. It also provides direction for future research on the issues of flexibility in power systems planning.
Keywords: 330; Decarbonization; Energy transition; Generation expansion planning; Power plant mix; Power system flexibility; Variable renewable energy sources